Seasonal variation in sexual opportunities of Servaea incana jumping spiders. Issue 1 (2nd January 2018) - Mendez, Vivian; McGinley, Rowan H.; Taylor, Phillip W.
Abstract : Male reproduction is commonly constrained by the availability of females, and more specifically by opportunities to fertilise the ova that females carry. For species in which availability and reproductive value of females vary seasonally, males can benefit if able to time their peak reproductive period to match periods of maximum availability and value of females. In Servaea incana jumping spiders, virgin females are at a premium because, once mated, females of this species only rarely accept subsequent suitors. We studied a population of S. incana for 13 months and found strong seasonal patterns in population structure, with a distinct peak of sexual maturation in the autumn months. Consistent with the high value of virgin females, males matured earlier than females (protandry) such that most males were already mature and ready to mate as females began maturing. Further, as is common in jumping spiders, adult males were found to cohabit with subadult females that were about to mature. As the season progressed, subadult females became less abundant and adult males were then sometimes found to cohabit with mated females. Despite protandry, the average size of adult males sampled during the first months of the year was greater than the average size of adult males sampled later, suggesting that adult males maturing at the beginning of the year tend to be larger than adult males maturing later. This finding is inconsistent with a hypothesised trade-off between early development and body size. We discuss the implications of protandry, cohabitation and mating-induced sexual inhibition in the mating system of this spider.